E-module for physics using Smart Apps Creator Software with internalization of soft skills - Armela, Kiki Rizki; Rosidin, Undang; Viyanti, Viyanti (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to develop an interactive e-module based on Smart Apps Creator software, focusing on the internalization of soft skills (creativity/innovation, problem-solving, teamwork, and personal effectiveness) in understanding the concepts of physics on work and energy material. The research method followed the 4-D development model but was limited to the development stage (Develop). The findings show that the developed e-module is deemed